2020
DOI: 10.1128/jvi.01923-19
|View full text |Cite
|
Sign up to set email alerts
|

PIWIL4 Maintains HIV-1 Latency by Enforcing Epigenetically Suppressive Modifications on the 5′ Long Terminal Repeat

Abstract: Although substantial progress has been made in depicting the molecular pathogenesis of human immunodeficiency virus type 1 (HIV-1) infection, the comprehensive mechanism of HIV-1 latency and the most promising therapeutic strategies to effectively reactivate the HIV-1 latent reservoir to achieve a functional cure for AIDS remain to be systematically illuminated. Here, we demonstrated that piwi (P element-induced Wimpy)-like RNA-mediated gene silencing 4 (PIWIL4) played an important role in suppressing HIV-1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…PIWIL4 , on chromosome 15, has been identified in the chromatin pathway [59, 60], where human PIWIL4 has a role in regulating gene expression in immune cells with gene silencing [61]. In vitro experiments showed that PIWIL4 knockdown in primary human cells from people with HIV-1 on suppressive combined antiretroviral therapy had increased HIV-1 transcription and reversed HIV-1 latency in HIV-1 latently infected Jurkat T cells and primary CD4+ T lymphocytes, as well as resting CD4+ T lymphocytes [62]. Mutations in CUL5 , also located on chromosome 15, have been associated with more rapid loss of CD4+ T cell in HIV infected patients [63].…”
Section: Discussionmentioning
confidence: 99%
“…PIWIL4 , on chromosome 15, has been identified in the chromatin pathway [59, 60], where human PIWIL4 has a role in regulating gene expression in immune cells with gene silencing [61]. In vitro experiments showed that PIWIL4 knockdown in primary human cells from people with HIV-1 on suppressive combined antiretroviral therapy had increased HIV-1 transcription and reversed HIV-1 latency in HIV-1 latently infected Jurkat T cells and primary CD4+ T lymphocytes, as well as resting CD4+ T lymphocytes [62]. Mutations in CUL5 , also located on chromosome 15, have been associated with more rapid loss of CD4+ T cell in HIV infected patients [63].…”
Section: Discussionmentioning
confidence: 99%
“…PIWIL4 , on chromosome 15, has been identified in the chromatin pathway [ 67 , 68 ], where human PIWIL4 has a role in regulating gene expression in immune cells with gene silencing [ 69 ]. In vitro experiments showed that PIWIL4 knockdown in primary human cells from people with HIV-1 on suppressive combined antiretroviral therapy had increased HIV-1 transcription and reversed HIV-1 latency in HIV-1 latently infected Jurkat T cells and primary CD4+ T lymphocytes, as well as resting CD4+ T lymphocytes [ 70 ]. Mutations in CUL5 , also located on chromosome 15, have been associated with more rapid loss of CD4+ T cell in HIV infected patients [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were stored at −80°C until the next step. Finally, proteolytic digests were dissolved into 0.01% formic acid and subjected for nanoscale LC-MS/MS with an EASY-nLC system connected to a Q-Exactive device with higher collisional dissociation fragmentation (Thermo Fisher Scientific) to characterize the differentially expressed proteins among the cell lines as previously described ( 66 ). The LC-MS/MS data were analyzed with PEAKS 6 Studio software (BSI, Canada).…”
Section: Methodsmentioning
confidence: 99%